Model of Green HRM Practice Implementation in Household Industries Based on Sustainable Local Wisdom: A Study on Cap Tikus Traditional Beverage Business in Talaitad Village, Suluun Tareran District - Jeaneta, Rumerung; Deky, Mundung; Muhammad, Bakary; Mikke, Marentek (International Journal Labs, 2025)
Environmentally friendly human resource management as part of local business sustainability efforts, especially those that are still traditional and based on community cultural values, has a strategic role. This study addresses the lack of structured Green HRM models within traditional local industries in Indonesia, particularly in household-scale businesses that operate based on cultural heritage and community values. The concept of Green Human Resource Management (Green HRM) is the application of human resource management that is environmentally friendly and can be implemented in the management of household industries that have a small business scale. The production process of Cap Tikus drinks has traditionally not considered the principles of sustainability and environmental friendliness. The purpose of the research is to identify green HRM practices that have been applied in the traditional beverage business, describe challenges in the implementation of green HRM, and formulate a model for implementing green HRM practices based on local wisdom and business sustainability. The results of the study show that the business management of the traditional beverage household industry is still traditional and has not implemented green HRM in business management. The application of the green HRM model is implemented through the practices of Green Recruitment & Selection, Green Training & Development, Green Performance Evaluation, and Green Employee Relations. The positive impact of the implementation is the formation of a working group that is concerned and environmentally friendly, competent and innovative in business management based on local wisdom, environmentally friendly practices, and optimal waste management.